Smart Out-of-Home Advertising Using Artificial Intelligence and GIS Data - Nader, Nader; Alexandrou, Rafael; Iasonas, Iasonas; Pamboris, Andreas; Papadopoulos, Harris; Konstantinidis, Andreas (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
This demonstration paper introduces the Smart Out-of-Home Advertising Platform (SOAP), which leverages Geographic Information Systems (GIS) data and state-of-the-art Artificial Intelligence (AI) approaches to provide: (i) a documented, data-informed pricing model for billboards, which can be used to justify billboard prices to advertisers; and (ii) a set of non-dominated solutions (each corresponding to a different allocation of billboards to a given campaign) that explores the trade-offs between multiple conflicting objectives (e.g., cost and coverage). To the best of our knowledge, SOAP is the first to tackle such challenges in the context of Multi Objective Optimization (MOO).